Stages of Historical Development of the Justifiable Defence Institute in the Criminal Law of Post Revolutionary Russia - E. I. Buyevich (Сибирское юридическое обозрение, 2013)
This article deals with the development of the criminal legislation of the justifiable defence. Attention is paid to the stage of development of this institute in the post revolutionary Russia. The history of the justifiable defence is subdivided into two stages: the soviet period and the post soviet period. The stages are defined according to the criterion of the main sources containing the features of justifiable defence.